The Efficiency With Which Information And Communication Technologies Is Used In Islamic Education To Recruit Potential Police Officers - Ahmad Rudy Sihaloho; Syukur Kholil; Ahmad Tamrin Sikumbang (Edukasi Islami: Jurnal Pendidikan Islam, 2022)
The North Sumatra Regional Police launched the Android-based SIBETAH application to ensure transparency and objectivity in selection. The purpose of this research is to thoroughly investigate the efficiency with which information and communication technologies is used in islamic education to recruit potential police officers, specifically what occurred in the North Sumatra Regional Police (POLDASU).A qualitative approach was used in this study, and this type of descriptive research was used because the researcher wanted to explore information from various groups, such as the recruitment committee, prospective members or parents of prospective members who participated in the registration, as well as the general public's views on Sumatra Regional Police's online technology-based recruitment activities. The data were analyzed using descriptive approaches in accordance with the study's design, which is a qualitative research. In this study, data analysis was performed before inputting data, while in the field, and after the field was completed.Communication and IT in recruitment to enhance Islamic community trust in North Sumatra Regional Police. The North Sumatra Police launched the SI BETAH application to: (a) provide public services that are easily accessible to the public based on information technology; (b) provide recruitment participants and the public with up-to-date information about the police officers recruitment process; and (c) accept a clean, transparent, accountable, and humane police officers. The implementation survey reveals public trust in the North Sumatra Regional Police institution is rising